Outcomes of Trabeculectomy and Glaucoma Drainage Devices for Elevated Intraocular Pressure After Penetrating Keratoplasty. Issue 6 (June 2018) - Yakin, Mehmet; Eksioglu, Umit; Yalniz-Akkaya, Zuleyha; Uzman, Selma; Singar-Ozdemir, Evin; Gultekin, Kemal; Demirok, Gulizar; Yalvac, Ilgaz; Ornek, Firdevs; Burcu, Ayse
Abstract : Purpose: To assess and compare the outcomes of trabeculectomy with and without antimetabolites (AMs) and glaucoma drainage devices (GDDs) in the management of elevated intraocular pressure (IOP) after penetrating keratoplasty (PK). Methods: Data of 84 eyes of 81 patients who underwent trabeculectomy (12 eyes without an AM and 42 eyes with an AM) or GDD implantation (30 eyes) after PK were reviewed retrospectively. The main outcome measures were IOP control, corneal graft survival, and postoperative ocular complications. Results: At the final visit, IOP success (<22 mm Hg) was 58.3% in trabeculectomy alone, 64.3% in trabeculectomy with an AM (TrabAM), and 86.7% in GDD groups ( P = 0.047). The median time from surgery to IOP failure was 1 month after trabeculectomy alone, 13 months after TrabAM, and 20 months after GDD implantation ( P = 0.042). The cumulative probability of IOP success rates at 1 and 3 years postoperatively was as follows: 66.7% and 57.1% in trabeculectomy alone, 80.6% and 64.8% in TrabAM, and 92.3% and 84.6 in GDD groups ( P = 0.063). The cumulative probability of corneal graft survival rates at 1 and 3 years postoperatively was as follows: 70.0% and 60.0% in trabeculectomy alone, 76.7% and 67.7% in TrabAM, and 65.8% and 52.6% in GDD groups ( P = 0.549). Conclusions: GDDs are more successful than trabeculectomy in controlling IOP in eyes that have undergone PK, but they tend to have low corneal graft survival rates. Trabeculectomy without an AM has limited success and may be considered in a limited number of patients with a low risk for bleb failure. Abstract : Supplemental Digital Content is Available in the Text.